Research Assessment of Iranian Medical Universities, an Experience from a Developing Country - H Malekafzali; MB Eftekhari; N Peykari; F Sadat Gholami; Sh Djalali nia; P Owlia; E Habibi; B Mesgarpour; M Vasei (Tehran University of Medical Sciences, 2009)
International ranking of universities by bibliometric assays has received a great attention in recent years. The developing countries have commenced to build their own infrastructure of research and post graduate training during the past couple of years. In 2000, the Ministry of Health and Medical Education of Iran began an annual national survey for assessing research activities in medical universities and their affiliated institutions by applying a customized ranking method. Research indicators were scored in three topics; Stewardship, Capacity Building, and Knowledge Production. In 2000, there were about 300 published medical articles in ISI/Thomson and PUBMED from the whole country. This number increased up to 3376 in 2007. The score of indexed papers in international databases per academic member rose from 0.1 in 2000 to 0.63 in 2007. The share of global articles (in the field of Medicine) grew from 0.06% in 2000 to 0.55% in 2007. This rising in article output led to a change from grade 57th in 2000 to 27th in 2007 in the ranking system of Scopus database. The number of local medical journals, which were 53 in 2000, increased to 141 at the end of 2008.  This rising scores was ongoing while the growth of the total staff of the academic members was about 25% (from 9086 in 2000 to 11324 in 2007). The number of the short training courses rose from 458 in 2000 to 1097 in 2007. The registered research projects in health topic rose from less than 3878 in 2000 to 6816 in 2007.